Boiling stable acid phosphatases (BsAPases) in Triticum aestivum induced by phosphate (Pi) deficiency - Sharma, Arun Dev; Rakhra, Gurmeen; Singh, Jatinder (Acta Biologica Szegediensis, 2012)
Nutrient limitation represents a ubiquitous form of environmental abiotic stress and Pi limitation is especially common due to low availability in most soils. As a result, most natural soils have soluble Pi concentrations lower than cytoplasmic Pi concentrations required for plant growth. Acid phosphatases (APases) are widely found in plants having intracellular and extracellular activities. APases are believed to be important for Pi scavenging and remobilization in plants, but role of boiling stable APases in adaptation to Pi stress at germination level has not been critically evaluated. To address this issue, the effect of low phosphate stress (LPS) on boiling stable acid phosphatases in wheat embryos and endosperm was investigated. With comparison to high phosphate condition (HP), a considerable increase in boiling stable acid phosphatase (BsAPase) activity was observed both in embryos and endosperm under LPS treatment. Post-LPS study revealed that BsAPase activity decreased considerably upon relieving the Pi stress. Further, as compared to HP conditions, SDS-PAGE analysis also detected a differential strong band under LPS conditions, which disappeared upon relieving Pi stress. These findings suggest that changes in the phosphatase enzymes might play important roles in adaptation of germinating seeds under Pi stress conditions. Based upon these results, a possible physiological role of BsAPases in germinating wheat seeds is discussed.